Systemic overuse of health care in a commercially insured US population, 2010–2015 - Oakes, Allison H. (BMC Health Serv Res, 2019)
BACKGROUND: Overuse is a leading contributor to the high cost of health care in the United States. Overuse harms patients and is a definitive waste of resources. The Johns Hopkins Overuse Index (JHOI) is a normalized measure of systemic health care services overuse, generated from claims data, that has been used to describe overuse in Medicare beneficiaries and to understand drivers of overuse. We aimed to adapt the JHOI for application to a commercially insured US population, to examine geographic variation in systemic overuse in this population, and to analyze trends over time to inform whether systemic overuse is an enduring problem. METHODS: We analyzed commercial insurance claims from 18 to 64 year old beneficiaries. We calculated a semiannual JHOI for each of the 375 Metropolitan Statistical Areas and 47 rural regions of the US. We generated maps to examine geographic variation and then analyzed each region’s change in their JHOI quintile from January 2011 to June 2015. RESULTS: The JHOI varied markedly across the US. Across the country, rural regions tended to have less systemic overuse than their MSA counterparts (p < 0.01). Regional systemic overuse is positively correlated from one time period to the next (p < 0.001). Between 2011 and 2015, 53.7% (N = 226) of regions remained in the same quintile of the JHOI. Eighty of these regions had a persistently high or persistently low JHOI throughout study duration. CONCLUSIONS: The systemic overuse of health care resources is an enduring, regional problem. Areas identified as having a persistently high rate of systemic overuse merit further investigation to understand drivers and potential points of intervention. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12913-019-4079-0) contains supplementary material, which is available to authorized users.